EFFECTIVENESS OF SPECIAL EFFORTS (UPAYA KHUSUS OR UPSUS) POLICY TO INCREASE RICE PRODUCTION IN SIDOARJO - Syaifudin, Arif Syaifudin (Universitas Muhammadiyah Jember, 2020)
Sidoarjo Regency is a fertile agricultural area as a food granary, maintaining advanced agriculture to be food self-sufficiency. However, the area of technical rice fields and rice production in Sidoarjo Regency from 2015 to 2017 had decreased. This is a challenge for sustainability to achieve food security. Thus, the formulation of the problem in this study was regarding the factors causing the ineffectiveness of Special Efforts (in Indonesian Upaya Khusus, abbreviated as UPSUS) for increasing rice production in Sidoarjo Regency. This study is a descriptive study that employed a qualitative approach. Thus, the data were collected through in-depth interviews technique on the informants from the Sidoarjo Regency Agriculture and Food Security Office and the Head of Farmer Association who came from Tarik, Jabon, Sedati, and Waru sub-districts. The data then were analyzed using an interactive analysis of Miles and Huberman. The results of this study explain that the factors that support the implementation of UPSUS policy in Sidoarjo Regency included the availability of agricultural officers/ extension officers in the field for UPSUS assistance, the carrying capacity of government both at village and sub-district level to UPSUS program, farmerâ€™s association that had been formed well as one of the supporting factors, technical irrigation support in Sidoarjo, and the availability of facilities and infrastructure both in the form of assistance and in the form of supply such as seeds, agricultural machine, and pest poison.Â